2019
DOI: 10.1016/j.carbon.2019.01.089
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced thermoelectric performance of twisted bilayer graphene nanoribbons junction

Abstract: We investigate the electron transport and thermoelectric property of twisted bilayer graphene nanoribbon junction (TBGNRJ) in 0 o , 21.8 o , 38.2 o and 60 o rotation angles by first principles calculation with Landauer-Buttiker and Boltzmann theories. It is found that TBGNRJs exhibit negative differential resistance (NDR) in 21.8 o and 38.2 o rotation angles under ±0.2 V bias voltage. More importantly, three peak ZT values of 2.0, 2.7 and 6.1 can be achieved in the 21.8 o rotation angle at 300K. The outstandin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Inorganic flexible TE materials, including CNTs, ceramics, and 2D materials, could be processed into freestanding thin films or deposited on flexible substrates . Among them, graphene attracts much attention recently in the application of FTEGs, due to its good mechanical properties, high electrical conductivity, and high theoretic calculation result of figure‐of‐merit . However, its low Seebeck coefficient and high thermal conductivity impede the TE application.…”
Section: Functional Components Of Stimesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic flexible TE materials, including CNTs, ceramics, and 2D materials, could be processed into freestanding thin films or deposited on flexible substrates . Among them, graphene attracts much attention recently in the application of FTEGs, due to its good mechanical properties, high electrical conductivity, and high theoretic calculation result of figure‐of‐merit . However, its low Seebeck coefficient and high thermal conductivity impede the TE application.…”
Section: Functional Components Of Stimesmentioning
confidence: 99%
“…Apart from the bottleneck of materials properties, the harsh processing conditions also impede the scalable production of devices based on many TE materials like rGO. In response to this issue, our group has successfully fabricated the TE device by a low‐temperature and solution‐based method 182b. A wristband‐type TEG was prepared by connecting seven bendable rGO‐based grids electrically in series.…”
Section: Functional Components Of Stimesmentioning
confidence: 99%
“…Edge defects can also lead to the occurrence of spin-dependent Seebeck effect and the enhancement of charge and spin ZT 5 . A strong reduction of thermal conductance compared with the single graphene nanoribbon has been predicted in twisted bilayer graphene nanoribbon junctions and outstanding ZT values may be achieved in some specific configurations 31 .…”
Section: Thermoelectric Properties Of Graphene-like Nanoribbon Studiementioning
confidence: 98%
“…However, the Seebeck coefficients are usually low in perfect intrinsic ZNRs because the slope of transmission spectra vanishes for both spins near the Fermi level. Breaking the geometry symmetry of ZNRs may modulate the energy dependence of transmission 4,19,29,30 and enhance the Seebeck coefficients 4,5,23,31 . Furthermore, edge disorder may enhance the thermoelectric ZT by reducing dramatically phonon thermal transport but affecting only weakly the electronic conduction 23 .…”
Section: Thermoelectric Properties Of Graphene-like Nanoribbon Studiementioning
confidence: 99%
“…A recent study has reported a thermoelectric figure of merit (ZT) up to 1.4 with graphene and C 60 clusters synthesized by chemical vapor deposition (CVD) [92]. Another theoretical investigation revealed three peak ZT values of 2.0, 2.7 and 6.1 at 300 K, with a twisted bilayer graphene nanoribbon junction [93]. As shown in Figure 4, the search for new thermoelectric materials is growing exponentially, but some categories are more attractive than others.…”
Section: New Thermoelectric Materialsmentioning
confidence: 99%